Relating aging and autophagy - Sougata Ghosh Chowdhury; Rachayeeta Ray; Parimal Karmakar (EXCLI Journal : Experimental and Clinical Sciences, 2023)
The most common factor that contributes to aging is the loss of proteostasis, resulting in an excess amount of non-functional/damaged proteins. These proteins lead to various age-associated phenotypes such as cellular senescence and dysfunction in the nutrient-sensing pathways. Despite the various factors that can contribute to aging, it is still a process that can be changed. According to recent advances in the field of biology, the ability to alter the pathways that are involved in aging can improve the lifespan of a person. Autophagy is a process that helps in preserving survival during stressful situations, such as starvation. It is a common component of various anti-aging interventions, including those that target the insulin/IGF-1 and rapamycin signaling pathways. It has been shown that altered autophagy is a common feature of old age and its impaired regulation could have significant effects on the aging process. This review aims to look into the role of autophagy in aging and how it can be used to improve one's health.